2020
DOI: 10.1186/s12913-020-05640-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of low-value pediatric services in the Military Health System

Abstract: Background: Low-value care (LVC) is understudied in pediatric populations and in the Military Health System (MHS). This cross-sectional study applies previously developed measures of pediatric LVC diagnostic tests, procedures, and treatments to children receiving care within the direct and purchased care environments of the MHS. Methods: We queried the MHS Data Repository (MDR) to identify children (n = 1,111,534) who received one or more of 20 previously described types of LVC in fiscal year 2015. We calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…11 Modestly higher rates of low-value service delivery were identified among publicly insured and military-insured children. 12,33 Reyes et al, 14,15 Bronchiolitis, CAP, and asthma measures had a relatively high prevalence of low-value care among both cohorts. These are among the most common and costly conditions treated in the pediatric hospital setting 34 and are popular targets for quality improvement initiatives, yet low-value care persists.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…11 Modestly higher rates of low-value service delivery were identified among publicly insured and military-insured children. 12,33 Reyes et al, 14,15 Bronchiolitis, CAP, and asthma measures had a relatively high prevalence of low-value care among both cohorts. These are among the most common and costly conditions treated in the pediatric hospital setting 34 and are popular targets for quality improvement initiatives, yet low-value care persists.…”
Section: Discussionmentioning
confidence: 89%
“… 11 Modestly higher rates of low-value service delivery were identified among publicly insured and military-insured children. 12 , 33 Reyes et al, 14 , 15 using the PHIS database, created a report card to measure performance on the original measures included in the pediatric Choosing Wisely Campaign by the Society of Hospital Medicine among hospitalized patients and found that low-value care delivery ranged from 12% to 49% across these measures. Our work incorporates a broad set of hospital-based, pediatric, low-value care measures into a tool capable of sustaining these measurement efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fee-for-service payment system: many authors have observed that payment structures emphasizing volume over value, such as the fee-for-service (FFS) payment system, are linked to the provision of low-value care 6,14,16,17,36,39,40,46,47,57,59,[61][62][63][64][65] . The FFS payment system offers a perverse incentive that drives health care providers to provide low-value care 66 .…”
Section: Health Care System Factorsmentioning
confidence: 99%